"Judging a Book by Its Cover": The Dominance of Delivery Over Content When Perceiving Charisma. Issue 6 (December 2019) - Caspi, Avner; Bogler, Ronit; Tzuman, Ofir
Perceived charisma is an outcome of message content and delivery, where the latter dominates the former. Framing perception of charisma within dual-process theories, we suggest a rapid processing of delivery and a slow processing of content. We aimed to track the differential processing speed of content and delivery that accounts for the delivery dominance. In two laboratory experiments, we manipulated content and delivery. Participants reported perceived charisma after viewing a presentation (Experiment 1) or moment-by-moment during the presentation (Experiment 2). The results confirmed the immediate influence of delivery on perceived charisma that was later either supported or revised by the content. Theoretical and practical implications of the findings are discussed.